The refractive index dispersion and the optical constants of liquid crystal metal-free and nickel(II) phthalocyanines - Yakuphanoğlu, Fahrettin; Durmus, M; Okutan, M; Köysal, O; Ahsen, V (Elsevier, 2006)
Optical characterization of metal-free and nickel(II) phthalocyanines liquid crystals has been carried out using optical absorption spectra. The refractive index spectra of the metal-free and nickel(II) phthalocyanines liquid crystals show both normal and anomalous dispersion. The refractive index dispersion parameters, oscillator energy E-o, dispersion energy E-d, long wavelength refractive index n(infinity) and oscillator length strength S. were found to be 7.07eV, 11.76eV, 2.66, 5.15 x 1013 m(-2) for H2Pc and 6.83eV, 13.39eV, 2.97, 6.20 x 10 13 m(-2) for NiPc, respectively. The optical moments M-1 and M-3 of H2Pc and NiPc were found to be 1.66 and 1.96, 0.033 and 0.042 eV(-2), respectively. The real and imaginary parts of the liquid crystals were calculated. The real part of the dielectric constant of the liquid crystals is higher than that of the imaginary part. The UV-visible spectra of H2Pc and NiPc show some intense bands which are at ranges of 250-450 and 550-800 nm. The intensity and position of peaks observed change due to the inclusion of Ni(II) metal into H2Pc. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phthalocyanines; optical constants; liquid crystal; refractive index